MEWUJUDKAN REKONSILIASI DAN DEMOKRATISASI DI INDONESIA MELALUI AGAMA - Basyir, Basyir (Jurnal Dakwah Tabligh, 2018)
This research focuses on the realization of reconciliation and democratization of peace in Indonesia through religious literacy. The problem of society lately involves many elements of religion as a reference for society to react to an issue. Religion is used as a reference in taking policy, so that it is quite enough to look at religion as the only way in meeting the interests of a group or group. Therefore, this study is aimed to find out the realization of reconciliation and democratization through religion in creating a harmonious and peaceful life. The research applies qualitative method with descriptive analysis model. The data collection is done through documentation study, it means that the data are found out in library sources. The results of this study indicates that it is needed to build a holistic awareness on the reconciliation and democratization of Pancasilais in order to realize a safe and peaceful nation and state in accordance with the values of Pancasila.